Integrating Science Learning in Indonesian Curriculum: A Case Study at a Junior High School - Mohammad, Nhelbourne K.; Dianita, Ariyanti; Akrim (The Indonesian Institute of Science and Technology Research, 2024)
The 2013 Curriculum in Indonesia aimed to prepare individuals and citizens who were faithful, productive, creative, innovative, and practical, as well as actively contributing to society, region, state, and world civilization. Also, the change in the curriculum aimed to increase the students’ curiosity and active participation. This study focused on adopting and implementing the 2013 Curriculum for integrative science learning in secondary school at Muhammadiyah-1 Malang Junior High School in Malang City, Indonesia. Regarding teachers’ roles, the 2013 Curriculum was designed to improve teacher professionalism. However, existing literature did not show whether the teachers, learners, and schools were ready to adopt such a curriculum. Based on the analysis of the data obtained from the interviews, observations, and documentation from Muhammadiyah Secondary School, we found that the school could be ready to implement the 2013 Curriculum.